Effect of Substrate Temperature on the Electrical Properties of Al-doped Zinc Oxide Films Deposited on Polyethylene Terephthalate - Faraj, Mohammad G. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2022)
To prepare homogeneous thin films of zinc oxide (ZnO) doped with aluminum (Al) on a polyethylene terephthalate (PET) substrate at different temperatures (200-250 °C), the process is carried out by utilizing the chemical spraying pyrolysis approach. A study of the effects of substrate temperature on the Al-doped Zinc Oxide (AZO) films’ electrical characteristics and roughness is performed. The measurements of atomic force microscopy (AFM) shows that the root mean square (RMS) roughness of the AZO films is increased with the increase of PET substrate temperature. Hall measurements show that the electrical resistivity decreases as the substrate temperature increases. Upon the increment of substrate temperature, there is an increase in the carrier concentration value from 9.98 × 1019 to 5.4 × 1020 cm−3 and an increase in the carrier mobility value from 5.5 to 9.76 cm2.(V. S)−1.